Hubungan Antara Penggunaan Gadget Dengan Interaksi Pendidikan Pada Anak Usia 4-6 Tahun dalam Keluarga di Jorong Rambai Nagari Koto Malintang Kecamatan Tanjung Raya - Dinda Wulandari; Jamaris Jamaris (Jurnal Family Education, 2023)
The background of this research is the low educational interaction among children in Jorong Rambai Nagari Koto Malintang, Tanjung Raya District, within the family, which is suspected to be due to the high use of gadgets by children in Jorong Rambai Nagari Koto Malintang, Tanjung Raya District. This study aims to see the level of gadget use, see the level of educational interaction between children in the family, and see the relationship between gadget use and educational interaction in children aged 4-6 years in families in Jorong Rambai Nagari Koto Malintang, Tanjung Raya District. This type of research is a correlational quantitative method. The population of this research is parents. Sampling by cluster random sampling. Data collection techniques with questionnaires. Data analysis using the percentage formula and product moment. The results showed that the use of gadgets for early childhood was said to be high, the educational interaction of children in the family was said to be low, and there was a significant relationship between the use of gadgets and the educational interaction of children in the family. Suggestions to pay attention to the use of gadgets in children, the educational interactions of children in the family must be considered.